Establishing a Volunteer Doula Program Within a Nurse‐Midwifery Education Program: A Winning Situation for Both Clients and Students. (7th May 2015) - Munoz, Elizabeth G.; Collins, Michelle
Abstract : The use of labor doulas is beneficial for mothers and newborns, but availability and cost can be barriers. The Nashville Volunteer Doula Program was formed to provide labor support to clients of a faculty nurse‐midwifery practice. The volunteer doula pool is comprised of both nurse‐midwifery students who have trained as doulas and community doulas. Training and coordination of volunteers are managed by nurse‐midwifery students with faculty support. Students gain valuable exposure to providing supportive care during labor and birth, which augments their nurse‐midwifery education. This novel program operates at a low cost and offers benefits to students as well as women who use the doula service. This article is part of a special series of articles that address midwifery innovations in clinical practice, education, interprofessional collaboration, health policy, and global health